Reduced Cortisol Output during Public Speaking Stress in Ostracized Women - Weik, Ulrike; Ruhweza, Jennifer; Deinzer, Renate (Frontiers in Psychology, 2017)
Ostracism (being excluded or ignored) is experienced as unpleasant and distressing. In previous studies, an immediate pre-stress experience of ostracism induced by Cyberball, a virtual ball-tossing game, was found to inhibit cortisol reactivity to public speaking stress in female students. The present study examines whether the effect will persist when a 15-minute time gap between the Cyberball experience and subsequent psychological stress is introduced. N=84 women were randomly assigned to Cyberball ostracism vs. inclusion. 15 minutes after playing Cyberball, all women were subjected to public speaking stress. Salivary cortisol and mood were repeatedly assessed during the course of the experiment. These are the main findings of the study: Repeated measures ANCOVA revealed that public speaking stress resulted in a significant increase of cortisol in both groups (inclusion vs. ostracism). However, cortisol levels were significantly lower in the ostracism group. In earlier studies when Cyberball was played immediately before public speaking stress, the cortisol response to public speaking was completely suppressed in ostracized women. By introducing a waiting period between Cyberball and public speaking stress in the present study, the main effect of an ostracism induced reduction of cortisol remained, although both groups showed an increase of cortisol as a response to public speaking. These results again suggest that the experience of ostracism might inhibit hypothalamic-pituitary-adrenal (HPA) axis activity, thereby confirming previous results. The formerly observed total suppression of HPA responsiveness to public speaking, however, seems to be a rather short-term effect.